Effect of vitamin D and location of asprosin, spexin and meteorin-like antibodies in the liver of rats with isoproterenol-induced myocardial infarction - Erdogan, Mehmet Mustafa; Kocaman, Nevin; Kavak, Songuel Yerlikaya; Salcan, Tarik; Karakuzulu, Fatma Tuba (Springer, 2025)
PurposeCardiovascular diseases are one of the leading causes of death worldwide. Vitamin D (VITD) regulates cell proliferation, differentiation, apoptosis and angiogenesis. It boosts glutathione synthesis, reduces reactive oxygen species (ROS), protects tissues and exerts anti-inflammatory effects by lowering proinflammatory cytokines (IL-1 beta, IL-6, TNF-alpha) through VITD receptor activation. The aim of this study was to investigate the effects of VITD on liver tissue changes, oxidative stress and inflammation following myocardial infarction (MI) and ischemia/reperfusion (I/R) injury, focusing on its modulation of asprosin (ASP), spexin (SPX) and meteorin-like (METRNL) biomarkers to explore new therapeutic strategies.MethodsRats were divided into four groups (n=7): Control (I), MI (II), VITD (III), and MI + VITD (IV). MI was induced with 200 mg/kg isoproterenol, and VITD (50 IU/day) was administered for 14 days as treatment.ResultsHistopathologically; congestion, sinusoidal dilatation, necrotic hepatocytes and fibrosis, and immunohistochemically; ASP, SPX and METRNL immunoreactivity were examined in the liver tissues of rats. In the immunohistochemical examination of ASP, SPX and METRNL, the histoscore in the MI group was significantly higher compared to the control and VITD groups (p<0.001). The effect size of these differences was large.ConclusionASP, SPX, and METRNL can be used as immunohistochemical biomarkers in order to demonstrate ischemia reperfusion injury in the liver of rats with MI. When the findings are evaluated, the application of VITD, a cytoprotective antioxidant, appears to play an effective role in preserving the biochemical and histological properties of hepatocytes. VITD is considered to contribute significantly to the histopathological and biochemical preservation of liver tissue.
Keywords: Asprosin; Liver; Meteorin-like; Spexin; Vitamin D